INTEGRATION IOT AND BIM FOR TECHNOLOGY AND IOT ENVIRONMENT - Firmansyah, Arrio; Ilham, Ilham (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2025)
Abstract: This research focuses on technology and integration tools for IoT environments, with an emphasis on three main aspects: the integration of Building Information Modeling (BIM) and IoT, the utilization of real-time data, and the urban IoT framework. The integration of BIM and IoT enables a smarter and more efficient building management system by utilizing IoT data to monitor real-time building conditions and improve maintenance and operational processes. This research seeks to identify challenges and solutions for technology integration in increasingly complex IoT environments, while also offering guidance for practical implementation in the urban and building sectors. In this research, we use a literature analysis approach, the main process is to identify relevant sources, including articles, journals, conferences, books, and industry reports published in the last five years. The results of this study are an implication that the application of IoT device integration with BIM can help improve operational and maintenance efficiency, optimize construction management, improve safety and mitigate risks in a company. Keywords: building informations modelling(BIM); environment; internet of things(IoT)  Abstrak: Penelitian ini berfokus pada teknologi dan alat integrasi untuk lingkungan IoT, dengan penekanan pada tiga aspek utama: integrasi Building Information Modeling (BIM) dan IoT, pemanfaatan data real-time, dan kerangka kerja IoT perkotaan. Integrasi antara BIM dan IoT memungkinkan sistem manajemen bangunan yang lebih cerdas dan efisien dengan memanfaatkan data IoT untuk memantau kondisi real-time bangunan serta memperbaiki proses pemeliharaan dan operasional. Penelitian ini berupaya mengidentifikasi tantangan dan solusi integrasi teknologi dalam lingkungan IoT yang semakin kompleks, sekaligus menawarkan panduan untuk penerapan praktis di sektor perkotaan dan bangunan. Pada penelitian ini kami menggunakan metode pendekatan analisis literatur, proses utamanya adalah dengan mengidentifikasi sumber sumber relevan, meliputi artikel, jurnal, konferensi, buku, dan laporan industri yang dipublikasikan dalam lima tahun terakhir. Hasil dari penelitian ini yaitu didapatkan sebuah implikasi bahwa penerapan pengintegrasian perangkat IoT denan BIM dapat membantu meningkatkan efisiensi operasional dan pemeliharaan, optimasi manajemen kontruksi, peningkatan keselamatan dan mitigasi resiko pada sebuah perusahaan. Kata kunci: building informations modelling(BIM); environment; internet of things(IoT)